Crafts and design: dialogues and teaching practices (2019)
This article presents, since the study of the region particulary since craft product,how can be generated learning processes bringing students of Industrial design of theUniversidad Catolica de Pereira through different realities of production, culture andaesthetic. The principal aim is recognize the hand made objects as a form of creation inwich the paticular characteristics of the region play an important role for itsunderstanding as a cultural fact.Handmade objects are a cultural manifestation in terms of its creation, developmentand preservation should be noticed inside of the maker comunity context where, bothculture and technique, become in two principles of study toward the recognition of thehandy craft objects as aesthetics fact.